Effect of virtual reality therapy, combined with physiotherapy for improving motor proficiency in individuals with Down syndrome: A systematic review - Jessica Stander; Jennifer C. du Preez; Chantel Kritzinger; Natasha M. Obermeyer; Silke Struwig; Nikki van Wyk; Jessica Zaayman; Marlette Burger (AOSIS, 2021)
Background: Individuals with Down syndrome may struggle with anticipatory postural adjustments, and adapt slower to motor tasks and environmental changes, due to decreased motor proficiency. Objectives: To determine the effectiveness of virtual reality therapy (VRT), specifically Nintendo Wii, combined with physiotherapy or occupational therapy (OT) for improving motor proficiency in individuals with Down syndrome, compared to standard physiotherapy, OT or no intervention. Method: Nine computerised databases were searched from inception to July 2020. Methodological quality of randomised controlled trials and quasi-experimental studies was appraised using the physiotherapy evidence database (PEDro) scale and the Joanna Briggs Institute Critical Appraisal Checklist for Case Reports. Results: Two randomised controlled trials and four quasi-experimental studies were included, with an average PEDro score of 7.3. One included case study scored 5. This review included 345 participants. Motor proficiency includes balance, coordination, strength and agility. Agility showed a significant improvement after 5 (p = 0.01) or 24 (p 0.01) weeks. Strength showed a significant improvement after a 6- (p = 0.000) or 24-week intervention (p 0.05). Balance showed inconclusive results for adults, and significant improvement in children after 6 (p = 0.000), 8 (p 0.05) or 24 (p 0.003) weeks. One study (n = 155) showed that upper limb and bilateral coordination improved significantly after 24 weeks (p 0.003). Conclusion: Level II, III-1 and IV evidence suggested that VRT may be valuable to improve agility and strength in individuals with Down syndrome, and balance and coordination in children with Down syndrome. Clinical implications: It may be beneficial to use VRT in addition to standard physiotherapy or OT interventions for improving motor proficiency in individuals with Down syndrome.